Mapping of nepotism based on surname homonymity: the case of the University of Novi Sad - Lazić, Uroš (Sociološki pregled, 2020)
The aim of the research was to check whether there were statistical indications of the existence of nepotism at the University of Novi Sad. The data were used on the current scientific and teaching staff and a unique electoral list for the City of Novi Sad. The socalled Academic Homonymity Index (AHI) was calculated based on surname homonymity. According to the comparison, the University of Novi Sad is placed at the very top of the reference list of Italian universities ranked by the probability of presence of nepotism practice. Thereby, there is a number of factors suggesting that our coefficients are underestimated. At the faculty level of aggregation, the Faculty of Medicine is the leader, while the Academy of Arts, the Faculty of Economics and the Faculty of Philosophy also belong to the institutions whose AHI index is well above the university average. At the departmental level of aggregation, the highest AHI index is registered for: the Department of Serbian Language and Linguistics, the Department of Energy and Process Engineering and the Music Department. A very high AHI index was also found for: the Department of Veterinary Medicine, the Department of Canned Food Engineering and the Department of Psychology. A new university law was proposed which would ban the employment of relatives in the same department, as well as a set of long-term measures in order to combat this problem.